ALQUR’AN DAN ETIKA BERBISNIS - Nursyamsu, Nursyamsu (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
One of the activities in carrying out economic activity is doing business, in the business needed values, so as not to be separated from the corridors that can lead to a business activity does not provide benefits, even bring harm. Business values in economic activities are necessary as the main rule in running a business activity. As a hint, the Qur’an is a major source in which various rules govern how to carry out business activities. Ethics is seen as a must-have on any business activity that can be seen in the behavior of a businessperson. This paper discusses the ethics of business in the perspective of the Qur’an.